A Clinical Study of Patients with Acute Epiglottitis - Kono, Michihisa; Goto, Takashi; Bandoh, Nobuyuki; Harabuchi, Yasuaki (International Journal of Practical Otolaryngology, 2018)
Acute epiglottitis is an acute inflammation of the upper respiratory airway that rarely causes airway obstruction. A retrospective study was conducted on 115 patients with acute epiglottitis from April 2007 to December 2017 (65 males and 50 females; aged 12–85 years old, median age of 45 years). When counting the number of patients according to the month, from April to September more than 10 patients were treated. Median duration from symptom onset to first visit was 3 days (1–14 days). Eight (7%) of 115 patients had diabetes, and 16 (13.9%) had epiglottic cyst. We divided all the patients into six groups by laryngeal findings according to the classification of Katori and Tsukuda. Number of patients classified as IA, IB, IIA, IIB, IIIA, and IIIB was 41 (35.7%), 21 (18.3%), 22 (19.1%), 15 (13%), 8 (7%), and 8 (7%), respectively. Median duration of hospitalization was 5 days (2–26 days). In the blood test on the first day of hospitalization, the number of white blood cells (WBC) ranged from 3,400 to 25,350/μL (median 10,350/μL) and the C-reactive protein (CRP) ranged from 0.01 to 23.3 mg/dL (median, 2.5 mg/dL). The number of WBC and CRP at the fourth day after the hospitalization was significantly lower than those at the first day. Eight (7%) patients required the airway management such as tracheotomy or cricothyroidotomy. Age, laryngeal finding (severe epiglottis swelling and arytenoid edema; Katori and Tsukuda's classification IIIB), and high inflammatory reaction in blood test (WBC ≥ 20,000/μL and CRP ≥ 20 mg/dL) were the factors that significantly correlated with the airway management.
Keywords: acute epiglottitis; airway management; laryngeal finding; inflammatory reaction in blood test; tracheotomy